Physical activity in sports clubs of children and adolescents in Germany: Results from a nationwide representative survey. - Jekauc, Darko; Reimers, Anne Kerstin; Wagner, Matthias Oliver; Woll, Alexander (Journal of Public Health, 2013)
Aim A substantial proportion of children’s and adolescent’s physical activity takes place in organised sports clubs in Germany. The purpose of this study was to describe (1) the proportion of children and adolescents who are members of sports clubs and the amount of moderate to vigorous physical activity (MVPA) performed in these clubs, and to identify socio-demographic predictors of (2) membership and (3) the amount of MVPA in sports clubs in Germany. Subjects and methods The sample consisted of 4,529 boys (50.5 %) and girls (49.5 %) aged between 4 and 17 years (M = 11.3; SD = 4.1). MVPA was assessed by a questionnaire. Socioeconomic status, immigration background, and resi- dential area were assessed using a parent questionnaire.Results 52.0 % of the girls and 63.1 % of the boys were members in sports clubs who exercised on average for 4 h per week with moderate to high intensity. The logistic regression analyses showed that gender, socioeconomic status, migration background and residential area were significant predictors of membership in sports clubs. The amount of MVPA was only significantly predicted by age, gender and residential area.Conclusion The results of this study imply that sports clubs have a high potential for implementation of strategies to increase general levels of physical activity.
Keywords: Physical activity; Sports club; Children; Adolescents; Germany